Determination of a Critical Angle (θc) for Track Revelation for Different CR-39 Nuclear Track Detector Materials - Ismail, Asaad H. (Sulaimani Journal for Pure and Applied Sciences, 2009)
Different thicknesses of 50 samples of commercially CR-39 Solid State Nuclear Track Detectors (SSNTDs) have been prepared with different ages and from different produced companies. Track parameters and plotting profiles, using computer program TRACK_TEST ware calculated. Detector efficiency has been found to be depends strongly on the critical angle for track revelation (C). On the other hand, critical angle depends strongly on the bulk etch rate.The results were specified that the detectors older than 3 years seemed to show odd behaviors of VB with detector efficiency. For age=3years the efficiency decreases exponentially for different alpha particle energy, and the bulk etch rate (VB ) increases with decreasing age. This behavior may be important in applications of this detector; for example, the calibration factor for radon measurements should be established by taking into account the age of the detector
Keywords: CR39 detectors; TRACKTEST program; Critical angle and Detector efficiency